Elevated expression of tumour necrosis factor‐α‐induced protein 8 (TNFAIP8)‐like 2 mRNA in peripheral blood mononuclear cells is associated with disease progression of acute‐on‐chronic hepatitis B liver failure. Issue 1 (16th May 2013) - Wang, L.‐Y.; Fan, Y.‐C.; Zhao, J.; Gao, S.; Sun, F.‐K.; Han, J.; Yang, Y.; Wang, K.
Summary Aberrant immunity response contributes to the pathogenesis of acute‐on‐chronic hepatitis B liver failure. Tumour necrosis factor‐α‐induced protein‐8 like‐2 (TIPE2) is a recently identified molecular to maintain immune homoeostasis, but its role in acute‐on‐chronic hepatitis B liver failure (ACHBLF) is unknown. We detected TIPE2 mRNA levels in peripheral blood mononuclear cells (PBMCs) from 56 patients with ACHBLF, 60 chronic hepatitis B patients, 24 healthy controls and analysed its role in disease severity and prognosis. TIPE2 mRNA expression in patients with ACHBLF was higher than that of patients with chronic infection or healthy controls. In patients with ACHBLF, TIPE2 mRNA level was positively correlated with serum total bilirubin, international normalized ratio and model for end‐stage liver disease scores. Furthermore, the level of TIPE2 mRNA was significantly higher in nonsurvivors than survivors in patients with ACHBLF. The mRNA level of TIPE2 gradually decreased week by week in survivors accompanied by recovery from patients with ACHBLF, while its expression sustained at high levels in nonsurvivors. TIPE2 mRNA level after lipopolysaccharide (LPS) stimulation ex vivo in patients with ACHBLF was higher compared with controls and patients with chronic infection. Meanwhile, cytokines ex vivo secreted were measured as a marker of immune activation. After LPS stimulation, interleukin (IL)‐6 and tumour necrosis factor (TNF)‐α mRNA expression were reduced in patients with ACHBLF, and a significantly negative correlation was found between TIPE2 and TNF‐α mRNA levels. In conclusion, our results identified the potential role of TIPE2 in predicting disease progression and prognosis in patients with ACHBLF by negative regulating of cell‐mediated immunity.